Generative AI in Tertiary Education - Marlene Miglbauer (Medienimpulse)
Taking a small teacher training college in Austria as a case study, this paper explores how students use generative AI tools for their studies, the challenges and opportunities genAI presents for teaching and how the institution responds to these challenges. Drawing on survey data and expert interviews, findings reveal that students frequently use genAI tools for academic tasks but often lack the necessary competencies. University teachers face didactic and legal challenges, while the university propagates for AI integration into curricula and professional development, emphasizing the importance of supporting teachers and students for successful AI adoption in tertiary education.